Inter-protein distances within the large subunit from Escherichia coli ribosomes. - May, R P (1992)
Selected pairs of protonated ribosomal proteins were reconstituted into deuterated 50S subunits from Escherichia coli ribosomes. The rRNA of the deuterated ribosomal matrix was derived from cells grown in 76% D2O, the deuterated protein moiety from cells grown in 84% D2O. This procedure warrants that the coherent neutron scattering of deuterated proteins and rRNA is nearly the same and equals that of a D2O solution of approximately 90%. The neutron scattering is recorded in a reconstitution buffer containing approximately 90% D2O. The result is a significant improvement of the coherent signal:noise ratio over traditional methods; due to this dilute solutions can be used, thus preventing unfavorable inter-particle effects. From the diffraction pattern the distance between the mass centers of gravity of the two protonated proteins can be deduced. In this way, 50 distances between proteins within the large subunit have been determined which provide a basis for future models of the large ribosomal subunit describing the spatial distribution of the ribosomal proteins. A model containing seven ribosomal proteins is presented.